Analisis Alih Kode dan Campur Kode dalam Media Sosial Twitter Akun @KuntoAjiW - Nabilla Rahma (Dinasti Research, 2023)
The mastery of more and more languages ​​causes a change in the use of one language with another in the communication process. The use of languages ​​with different ethnic backgrounds will also provide different language variations in the communication process. One of the language variations is in the form of code switching and code mixing. Code switching and code mixing are the changing of a particular language or variety of language into another language. Code switching and code mixing can occur in bilingual or multilingual communities. Language mixing occurs in the context of formal and non-formal speech. Code switching and code mixing can not only occur in direct speech, but can also occur in social media, especially Twitter. This study aims to identify forms and describe the factors that influence the occurrence of code switching and code mixing on the Twitter account @KuntoAjiW. The method used in this research is descriptive qualitative method. Data was obtained through observation and documentation on social media Twitter. The results of this study are in the form of code switching and code mixing, as well as factors that influence code switching and code mixing on social media Twitter on the @KuntoAjiW account. The forms of code switching and code mixing contained in the @KuntoAjiW account are Indonesian, Javanese and English. Factors that influence the occurrence of code-switching and code-mixing on the @KuntoAjiW account are the habits of speakers, speech partners, the presence of third speakers, and the use of more popular terms and topics of conversation..